The impact of a training program on the improvement of some defensive skills of handball players (17_19) years. - sedira.saad; تمار محمد; لواتي عبد السلام (sports creativity, 2025)
This study is focused on the theme " the impact of a training program on improving certain defensive tactical skills in handball", a field study conducted on the players of some of the handball teams of the state (Province) league of Setif-Algeria. This study aimed to reveal the impact of the training program on the improvement of some defensive tactical skills in Handball, based on the experimental method planned on two groups : the experimental group and the control group for the a priori and a posterior measure/control, through the design of two identical groups so that the control group will consist of 11players as well as the experimental group (11handball players), and the two researchers used a training program applied to the experimental group.